1996
DOI: 10.1021/jo960962h
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Several Control Elements Relevant to the Stereodefined Serial Elaboration of Belted Poly(spirotetrahydrofurans) Fitted with a Cyclohexane Core

Abstract: The stereochemistry of the condensations of 2-cyclohexenones, alpha-arylidenecyclohexanones, and alpha-(tert-butyldimethylsiloxy)cyclohexanones carrying one or two (both syn and anti) spirotetrahydrofuran units adjacent to the carbonyl with allyl organometallics (especially indium) and with the Normant reagent (ClMgO(CH(2))(3)MgCl) is described. Good levels of anti stereoselection are observed in the alpha-arylidene series. Subsequent cyclization generates a second (or third) tetrahydrofuran ring possessing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
0
27
0
2
Order By: Relevance
“…With α,β-unsaturated aldehydes and ketones a regioselective 1,2-attack was observed in indium-mediated allyl additions (Scheme 16). 69 Nevertheless, Lee et al found that with certain cyclic enones [2-cyclohexen-1-one, (R)-carvone, 2-cyclohepten-1-one, or chalcone] a 1,4-allyl addition became dominant when chlorotrimethylsilane (TMSCl) was added, although yields did not exceed 70%. With 2-cyclopenten-1-one, 2-methylcyclopenten-1-one, 4,4-dimethylcyclohexen-1-one and with acyclic α,β-unsaturated enones exclusively 1,2-addition was observed.…”
Section: Regioselectivitymentioning
confidence: 99%
“…With α,β-unsaturated aldehydes and ketones a regioselective 1,2-attack was observed in indium-mediated allyl additions (Scheme 16). 69 Nevertheless, Lee et al found that with certain cyclic enones [2-cyclohexen-1-one, (R)-carvone, 2-cyclohepten-1-one, or chalcone] a 1,4-allyl addition became dominant when chlorotrimethylsilane (TMSCl) was added, although yields did not exceed 70%. With 2-cyclopenten-1-one, 2-methylcyclopenten-1-one, 4,4-dimethylcyclohexen-1-one and with acyclic α,β-unsaturated enones exclusively 1,2-addition was observed.…”
Section: Regioselectivitymentioning
confidence: 99%
“…Equatorial attack on the all-equatorial oxygen conformation of 4 is therefore overwhelmingly favored kinetically [5] (Scheme 1). As a consequence, the oxygen atom at this center must be introduced last.…”
mentioning
confidence: 99%
“…[3] As a component of the cell membrane, glycoconjugates fulfil important functions [2±4] during cell ± cell recognition, cell ± matrix interaction, and cell growth regulation, and thus also in the development of tumors. [5] Furthermore, they play a significant role in the interaction with biologically active factors such as enzymes, hormones, bacteriotoxins, and viruses. [1,4] The substructure of a carbohydrate, which undergoes permanent change [6] during the life cycle of a cell, influences the biological properties of peptides and proteins.…”
mentioning
confidence: 99%
“…Der äquatoriale Angriff auf 4 in der Konformation, in der alle Sauerstoffatome äquatorial stehen, ist daher eindeutig kinetisch bevorzugt [5] …”
unclassified